Social Capital and Women's Reduced Vulnerability to HIV Infection in Rural Zimbabwe. - Gregson, Simon; Mushati, Phyllis; Grusin, Harry; Nhamo, Mercy; Schumacher, Christina; Skovdal, Morten; Nyamukapa, Constance; Campbell, Catherine (Population & Development Review, 2011)
The writers assess the effect of community group membership on HIV incidence among men and women at the population level and individual level in eastern Zimbabwe. Their data were obtained from a population-based cohort study in communities in Zimbabwe that were subject to large generalized AIDS epidemics in sub-Saharan Africa. They describe recent patterns of group membership within the communities and find that membership levels are higher among women than men, and varied with political and socioeconomic instability. They demonstrate that these communities with greater social capital have lower levels of HIV incidence and less risky behavior patterns among women.